The significance and influence of religions and confessions on the formation of nations in Bosnia and Herzegovina. - Pehar, Antonio (Academicus, 2021)
The article deals with the religious and confessional identity of the population in Bosnia and Herzegovina at the time of Ottoman and then the Austro-Hungarian authorities, and it is trying to define the elements of nationality in their identity. The reasons for initiating the rounding-up of three national identities in Bosnia and Herzegovina (Muslim/Bosniak, Croatian and Serbian) and not a common one are also highlighted. It identifies the external factors as well as the circumstances of the internal dynamics of society that have influenced the formation of the nation on the dominant principle of religious/confessional affiliation of the population.